City - Scale Spatial Data Infrastructure for Solar Photovoltaic Energy Generation Assessment - Gowri Shankar Rao, R; K. Rayaguru, N; G.Renganathan, N; Kumar Thakur, Sunil (International Journal of Engineering and Technology, 2018)
Spatial data plays an vital role in decision-making for development of smart cities. As it is very evident that the development of smart and sustainable city mainly depends on its physical infrastructure such as intelligent transportation, smart energy, smart metering etc., This paper provides an analysis which aims using the spatial data infrastructure tools for estimation of the region based solar PV potential generation for a specific urban region . This analysis would afford a great insight in deciding a city scaled potential energy production and planning, an estimate of the geographical PV potentials for solar power generation is adopted. The total PV potential is evaluated for a specific defined area and compared with the local electricity demand. The outcomes comprise of an initial valuation of the town’s solar potential that can be used to upkeep organization decisions regarding reserves in solar systems. Successful implementation of SDI finally depends on the political governance and their framing policies.